Sinergi antara Good Government dan Azas-Azas Umum Pemerintahan Yang Baik (AAUPB) dalam Upaya Pencegahan Korupsi - Hakim, Husnul (DIALEKTIKA: Jurnal Ekonomi dan Ilmu Sosial, 2022)
Eradication of criminal acts of corruption cannot be carried out only by prosecuting the perpetrators and bringing them to the courtroom, but efforts to prevent corruption are needed. One of the actors with the potential to commit corruption, collusion and nepotism is government officials, therefore a work reference is needed in carrying out the authority of government officials so as to avoid acts of corruption. This research is also a method of monitoring the performance of government officials so as to prevent acts of abuse of authority that lead to acts of corruption. Supervision by the community, educational institutions together with government agencies is an effective way to prevent acts of corruption, one of which is through the application of the General Principles of Good Governance (AAUPB) which is an unwritten law and acts as signs in running the Government. The implementation of the AAUPB will automatically distance the authorized officials from acts of corruption in the government environment so that they can provide good services to the community.